SHOW STOPPERS: MOVIE CENSORSHIP CONSIDERED AS A BUSINESS PROPOSITION - Clayton Koppes (Essays in Economic and Business History, 2012)
Although censorship is usually interpreted as a matter of freedom of expression, censorship was also a major business concern during the heyday of the American movie industry. Manipulating censorship issues was essential to the industry’s economic health. The Production Code Administration (PCA), the industry’s in-house censorship agency, played a crucial role in maintaining order in Hollywood and fending off governmental control.